Building a Digital Entrepreneur Mindset Through Online Business Workshops for MSME Actors - Maimuna, Fransiska Fitria; Fawzan, Ryan Ahmad; Ramadhan, M Noval (Indonesian Journal Of Economy Studies, 2024)
The development of digital technology has created great opportunities for Micro, Small and Medium Enterprises (MSMEs) to develop. However, many MSMEs do not yet have the digital entrepreneurial mindset needed to utilize this technology optimally. This research aims to build a digital entrepreneurial mindset in MSME players through knowledge transfer methods in the form of online business workshops. Low levels of digital literacy and dependence on conventional business methods are the main challenges for MSMEs in adapting to the digital era. Through knowledge transfer, MSME players are given understanding and practical skills to utilize digital technology in business development. The research results show that the method of transferring knowledge through this workshop is able to increase MSME actors' understanding of digital technology and change their thinking patterns in a more innovative direction. This program is expected to be the first step in supporting the digital transformation of MSMEs to be more competitive in the global market.Keyword:Â Digital Entrepreneur, Online Business Workshop, MSMEs, Mindset, Digital Technology